Infiltrating cellular pattern in kidney graft biopsies translates into forkhead box protein 3 up‐regulation and p16INK4α senescence protein down‐regulation in patients treated with belatacept compared to cyclosporin A - Furuzawa‐Carballeda, J.; Lima, G.; Alberú, J.; Palafox, D.; Uribe‐Uribe, N.; Morales‐Buenrostro, L. E.; Reyes Acevedo, R.; Mondragón, G.; Chevaile, A.; Llorente, L. (Clinical and experimental immunology, 2012)
Summary Renal allograft survival is related directly to cell senescence. In the transplantation scenario many cellular events – participating as immunological and non‐immunological factors – could contribute to accelerate this biological process, responsible for the ultimate fate of the graft. Mechanisms concerned in tolerance versus rejection are paramount in this outcome. For this reason, immunosuppressive treatment constitutes an extremely important decision to prevent organ dysfunction and, finally, graft loss. This study was conducted to document the proportion of CD4+/interleukin (IL)‐17A+‐, CD16+/indoleamine 2, 3‐dioxygenase (IDO+)‐, forkhead box protein P3 (FoxP3+)‐expressing cells, senescent cells (p16INK4α) and the percentage of interstitial fibrosis (IF) in graft biopsies of kidney transplant recipients participating in the BENEFIT (Bristol‐Myers Squibb IM103008) study. CD4+/IL‐17A+, CD16+/IDO+, FoxP3+ and p16INK4α+ cells were evaluated by immunohistochemistry, and the percentage of IF by morphometry on graft biopsies obtained at time 0 (pre‐implantation) and at 12 months post‐transplant. Senescent cells and CD4+/IL‐17A+ cells were increased among graft biopsies in subjects receiving cyclosporin A (CsA) compared to those under belatacept treatment. Meanwhile, CD16+/IDO+ and FoxP3+‐expressing cells were lower in biopsies from CsA treatment compared to patients treated with Belatacept. Histological morphometric analyses disclosed more IF in 12‐month CsA‐treated patients in comparison to pre‐implantation biopsy findings. Summing up, renal biopsies from patients receiving belatacept showed greater amounts of FoxP3+ cells and lower amounts of CD4+/IL‐17A+ and senescent cells compared to patients under CsA treatment. Along with these findings, an increase in IF in annual CsA‐treated‐patients biopsies compared to pre‐implantation and belatacept‐treated patients were observed.